Synthesis and Characterization of Water Hyacinth Porous Carbon for Lithium Sulfur Battery Cathode Composites - Otong Nurhilal; Sahrul Hidayat; Risdiana . (Universitas Padjadjaran, 2023)
Water hyacinth as a weed plant is a type of biomass with a fast growth rate. This condition causes problems in the environment and has a negative impact on life, including health and economic problems. To provide added value to the utilization of water hyacinth, a synthesis and characterization of porous carbon from water hyacinth has been carried out which is used as a sulfur cathode matrix in lithium sulfur batteries. From the results of the N2 adsorption-desorption test, the surface area of porous carbon was 297.7 m2/g and the total pore volume was 0.332 cm3/g. The results of the composite test showed that the sulfur content in the composite for a ratio of 1:2.5 was 60.6 wt%. The cathode of a lithium sulfur battery has been made from a composite with a thickness 100 mm and a sulfur loading of 2.80 mg/cm2. The initial discharge capacity of the battery is 264 mAh/g with a coulomb efficiency of up to 70%. Battery discharge capacity of 175.5 mAh/g at 50th cycle.